Identification of essential genes for Escherichia coli aryl polyene biosynthesis and function in biofilm formation - Isabel Johnston (Nature Portfolio, 2021)
Abstract Aryl polyenes (APEs) are specialized polyunsaturated carboxylic acids that were identified in silico as the product of the most widespread family of bacterial biosynthetic gene clusters (BGCs). They are present in several Gram-negative host-associated bacteria, including multidrug-resistant human pathogens. Here, we characterize a biological function of APEs, focusing on the BGC from a uropathogenic Escherichia coli (UPEC) strain. We first perform a genetic deletion analysis to identify the essential genes required for APE biosynthesis. Next, we show that APEs function as fitness factors that increase protection from oxidative stress and contribute to biofilm formation. Together, our study highlights key steps in the APE biosynthesis pathway that can be explored as potential drug targets for complementary strategies to reduce fitness and prevent biofilm formation of multi-drug resistant pathogens.